2014
DOI: 10.1186/1479-5876-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Methods and matrices: approaches to identifying miRNAs for Nasopharyngeal carcinoma

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a solid tumor of the head and neck. Multimodal therapy is highly effective when NPC is detected early. However, due to the location of the tumor and the absence of clinical signs, early detection is difficult, making a biomarker for the early detection of NPC a priority. The dysregulation of small non-coding RNAs (miRNAs) during carcinogenesis is the focus of much current biomarker research. Herein, we examine several miRNA discovery methods using two sample matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 58 publications
2
54
0
Order By: Relevance
“…To address this problem, we extracted RNA using the miRNeasy serum/blood plasma kit (Qiagen), which uses phenol and chloroform, and as a positive control, spiked plasma with C. elegans miR-39 mimic (Qiagen) [16]. The yield of RNA derived from plasma in both the QIAamp and miRNAeasy methods was 8-12 ng/μl, and was of similar quality to that we have recovered from sera [17], although RNA from plasma exhibited lower 260/230 ratios, (<0.7) with the miRNeasy kit. However, when RNA isolated using miRNeasy was subjected to qPCR, the C t values did not improve, including for control C. elegans miR-39 which was employed to spike plasma (Figure 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…To address this problem, we extracted RNA using the miRNeasy serum/blood plasma kit (Qiagen), which uses phenol and chloroform, and as a positive control, spiked plasma with C. elegans miR-39 mimic (Qiagen) [16]. The yield of RNA derived from plasma in both the QIAamp and miRNAeasy methods was 8-12 ng/μl, and was of similar quality to that we have recovered from sera [17], although RNA from plasma exhibited lower 260/230 ratios, (<0.7) with the miRNeasy kit. However, when RNA isolated using miRNeasy was subjected to qPCR, the C t values did not improve, including for control C. elegans miR-39 which was employed to spike plasma (Figure 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reports confirmed the abundant expression of the BART miRNAs in NPC tissues in the absence of BHRF1 miRNAs. A recent study revealed that all 44 BART miRNAs were expressed in NPC tumours, at broadly similar levels (Plieskatt et al, 2014). Interestingly, approximately one-sixth of the total miRNA content in NPC cells attributed to BART miRNAs, suggesting that BART miRNAs provided a considerable portion of the total regulatory influence of both viral and cellular genes in NPC tumour cells (Lo et al, 2012).…”
Section: Bart Mirnamentioning
confidence: 98%
“…Number of Studies miRNAs Up 2 miR-15b (Chen et al, 2009;Plieskatt et al, 2014), miR-18a (Chen et al, 2009;Li et al, 2011), miR-205 (Chen et al, 2009Plieskatt et al, 2014), miR-25 (Chen et al, 2009;Plieskatt et al, 2014) 1 miR-106a (Chen et al, 2009), miR-1268a (Plieskatt et al, 2014), miR1268b (Plieskatt et al, 2014), miR-1303 (Plieskatt et al, 2014), miR-1304 (Plieskatt et al, 2014), miR-1305 (Plieskatt et al, 2014), miR-138 (Chen et al, 2009), miR-142-3p (Chen et al, 2009, miR-151 (Sengupta et al, 2008), miR-155 (Chen et al, 2009), miR-17 (Chen et al, 2009), miR-184 (Plieskatt et al, 2014), miR-192 (Sengupta et al, 2008), miR-196b (Chen et al, 2009, miR-21 (Plieskatt et al, 2014), miR-27a (Plieskatt et al, 2014), miR-378 , miR-4677 (Plieskatt et al, 2014), miR-4791 (Plieskatt et al, 2014), miR548n (Plieskatt et al, 2014), miR-6510 (Plieskatt et al, 2014), miR-92a (Plieskatt et al, 2014), miR-944 (Plieskatt et al,2014) Down 3 miR-34b (Chen et al, 2009;Li et al, 2011;Sengupta et al, 2008), miR-100 (Chen et al, 2009;Li et al, 2011;Plieskatt et al, 2014), miR-152 (Chen et al, 2009;Li et al, 2011;Plieskatt et al, 2014…”
Section: Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-376a has been reported to attenuate the proliferation and migration of melanoma cells by targeting IGF1R, a tyrosine kinase receptor associated with tumorigenesis and metastasis [8]. MiR-376a also regulates proliferation, apoptosis, migration and invasion in metastatic prostate cancer and hepatocellular carcinoma [9][10], and functions as a tumor suppressor in nasopharyngeal carcinoma [11]. Nevertheless, few studies have focused on the function of miR-376a in lung cancer, especially NSCLC, despite its significance to human health.…”
Section: Introductionmentioning
confidence: 99%